Exploring the Barriers and Motivations for Physical Activity Among Saudi Adults: A Qualitative Approach (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Although it is well known that physical activity provides numerous health benefits and enhances wellbeing, there is substantial evidence indicating that Saudi adults do not achieve public health guidelines. Therefore, recognising and addressing the barriers and enhancing motivations to indoor and outdoor physical activity is essential for promoting greater opportunities to engage in physical activity. The purpose of this study is to explore in depth the factors influencing indoor and outdoor physical activity among Saudi adults.Methods: A total of 22 Saudis (16 Saudi women and 6 Saudi men; ranged in age from 20 to 65 years, with an average age of 30 ± 10.1 years) took part in semi-structured interviews. The participants were conveniently recruited from different regions of Saudi Arabia to represent a variety of regional perspectives. The interview guide was based on the Socioecological Model of the determinants of physical activity to cover individual, interpersonal, environmental, and policy factors. All interviews were conducted in Arabic; thus, the first author transcribed all interviews in Arabic and then translated them to English. Both deductive and inductive approaches of qualitative content analysis were used for data analysis.Results: Data were coded into four main categories based on the Socioecological Model of the determinants of physical activity (individual, interpersonal, environmental, and policy). Then, 11 sub-categories related to barriers and eight sub-categories related to motivators were generated. These results show that physical activity behaviour of participants was negatively influenced by societal and environmental factors, including discouragement, poor facilities, and unsafe areas, with women particularly affected. On the other hand, personal and societal motivations, such as improving health, enhancing mood, and being part of active communities were identified as key motivators for engaging in physical activity.Conclusion: To increase physical activity levels in Saudi adults, interventions and policy modifications aimed at overcoming participation barriers and enhancing motivators are essential. Emphasis should be placed on overcoming societal and environmental barriers and enhancing personal and societal motivations.